Catalytic Synthesis of N‐Unprotected Piperazines, Morpholines, and Thiomorpholines from Aldehydes and SnAP Reagents. (23rd July 2015) - Luescher, Michael U.; Bode, Jeffrey W.
Abstract Commercially available SnAP (stannyl amine protocol) reagents allow the transformation of aldehydes and ketones into a variety of N‐unprotected heterocycles. By identifying new ligands and reaction conditions, a robust catalytic variant that expands the substrate scope to previously inaccessible heteroaromatic substrates and new substitution patterns was realized. It also establishes the basis for a catalytic enantioselective process through the use of chiral ligands.